Cosmeceutical science in clinical practice - Sadick, Neil S. (Series in cosmetic and laser therapy., 2010)
Cosmeceuticals are skin-care products that fall between a cosmetic and a pharmaceutical; that is, they have active ingredients that counter skin ageing and promote skin rejuvenation. As such, they are an invaluable adjunct to the cosmetic dermatologist or plastic surgeon performing minimally invasive aesthetic procedures.